Persistence with Antiplatelet and Risk of Major Adverse Cardiac and Cerebrovascular Events in Acute Coronary Syndrome Patients after Percutaneous Coronary Intervention in Indonesia: A Retrospective Cohort Study - Kristin, Erna; Kris Dinarti, Lucia; Yasmina, Alfi; Pratiwi, Woro Rukmi; Pinzon, Rizaldy Taslim; Indra Jaya, Sudi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Acute coronary syndrome (ACS) is a life-threatening condition that carries high risk of recurrent cardiovascular events and death. Persistence with treatment is known to reduce morbidity and mortality in patients with ACS. AIM: This study focuses on ACS patients undergoing their first percutaneous coronary intervention (PCI) to investigate the association between persistence with antiplatelet therapy and clinical outcomes. MATERIALS AND METHODS: A retrospective cohort study with 2 years of follow-up was conducted with 367 patients recruited. Patients were deemed as having persistence with antiplatelet therapy (WHO ATC code: B0A1C), if the gap between prescriptions was ≤30 days. The clinical outcomes were defined as a composite of major adverse cardiac event (MACE), major adverse cardiovascular and cerebrovascular events (MACCE), myocardial infarction, recurrent PCI, stroke, all-cause death, cardiovascular death, and hospitalization. RESULTS: Cumulative persistence with antiplatelet showed that 72.3% of all ACS patients were still taking antiplatelet 1 year after PCI. Persistence to treatment with antiplatelet therapy can be used as a predictor of MACE or MACCE, because it was associated with recurrent PCI (RR 3.09, 95% CI = 1.18−8.05). History of cardiovascular disease in non-persistence patients was associated with increased risk of MACE (RR 4.90 95% CI = 1.37−17.48) and MACCE (RR 3.67 95% CI = 1.12−11.98) events. CONCLUSION: After PCI, not all ACS patients continued taking their drug exactly as prescribed. Our study indicates that among ACS patients who underwent their first PCI, non-persistence with antiplatelet therapy might lead to worse clinical outcomes. This data will help promote secondary prevention among ACS patients after PCI.